Brucella pinnipedialis in hooded seal (Cystophora cristata) primary epithelial cells. Issue 1 (December 2015) - Larsen, Anett; Godfroid, Jacques; Nymo, Ingebjørg
Abstract Background MarineBrucella spp. have been isolated from numerous pinniped and cetacean species, but pathological findings in association with infection withBrucella pinnipedialis in pinnipeds have been sparse. The capacity of brucellae to survive and replicate within host macrophages underlies their important ability to produce chronic infections, but previous work has shown thatB. pinnipedialis spp. are rapidly eliminated from hooded seal (Cystophora cristata ) alveolar macrophages. Results To investigate if multiplication could take place in other hooded seal cell types, primary epithelial cells were isolated, verified to express the epithelial marker cytokeratin and challenged with three different strains ofB. pinnipedialis ;B. pinnipedialis sp. nov., B. pinnipedialis hooded seal strain B17, andB. pinnipedialis hooded seal strain 22F1. All strains were steadily eliminated and the amounts of intracellular bacteria were reduced to less than one-third by 48 h post infection. Intracellular presence was verified using immunocytochemistry. Conclusions So far, intracellular multiplication in seal cells has not been documented forB. pinnipedialis . The lack of intracellular survival in macrophages, as well as in epithelial cells, together with the fact that pathological changes due toB. pinnipedialis infection is not yet identified in seals, suggests that the bacteria may only cause a mild, acute and transient infection. These findings also contribute to substantiate the hypothesis that seals may not be the primary host ofB. pinnipedialis and that the transmission to seals are caused by other species in the marine environment.